A Novel Health Management Model for Search and Rescue (SAR) Teams During the Batang Kali Landslide, 2022: A Case Study of Public Health Response - Suhaida BT Mohd Sidek; Siti Syawakir Shamsuddin; Khairunnisa Ariffin; Nurfahzilah Abdul Aziz; Rosnawati; Mohamad Robat; Faridah Kusnin; Hazlina Yahaya; Thilaka Chinayah; Mohd Hisyamuddin Che Wan Naman; Rawlin Dundang Nyelang; Nurfazilah Abdul Wazir (ASEAN Journal of Disaster Health Management (AJDHM), 2025)
Introduction: A catastrophic landslide in Batang Kali, Hulu Selangor, Malaysia on December 16, 2022, displaced 16 million cu ft of soil, resulting in 61 rescues and 31 fatalities. Search and Rescue (SAR) team members face significant health risks and traumatic experiences during such operations. Objectives: This case study examines four key aspects of SAR operations, that is the efficacy of global health management for SAR teams, the physical and mental health implications on personnel during extended operations, the assessment of environmental health hazards in the disaster area and their mitigation measures, and the documentation of key lessons learned for future operational improvements. Methods: This is a case study on piloting innovative composite questionnaire on global assessment of health risks of SAR team members. The environmental health assessments were conducted using an adapted form from MOH Malaysia Guidelines for the Diagnosis, Management, Prevention and Control of Leptospirosis, 2011. The mental health using Whooley and GAD-2 questionnaires and the rest of the assessments including physical health using adapted MOH Malaysia Flood Preparedness Guidelines, 2008. Data was analysed using descriptive statistics. A one-stop health base was established for surveillance, coordination, and support. Results: Of 509 SAR team members, 56 (11%) participated. Physical health screening (n=18) revealed physical injuries (37.5%), hypertension (25%), mental health issues (25%), and one cardiovascular accident (12.5%). Mental health screening (n=29) identified three (10.3%) positive cases requiring counselling. Nine members attended Psychological First Aid sessions (44% psychoeducation, 33% relaxation, 23% sleep hygiene). No infectious diseases were reported during or one-month post-operation. Discussion & Conclusion: This novel model demonstrates effective comprehensive health monitoring during disaster response. The study supports pre- and post-deployment health screenings and improved interagency coordination, serving as a framework for future emergency responses.